Izzivi prenosa vodenja na naslednjo generacijo v družinskem podjetju (University of Maribor Press, 2025)
Challenges in Transferring Leadership to the Next Generation in a Family Business. The monograph “Challenges in Transferring Leadership to the Next Generation in a Family Business” brings together seven chapters within a unified scholarly framework—from a critical literature review and situational analysis to empirical research and practical initiatives—to examine the key dimensions of succession at Dines d. o. o. The opening chapter explores digital knowledge support, followed by discussions of career‐planning strategies, the 3C model (competence, cohesion, creativity) for leadership development, the digital transformation of procurement processes, the use of advanced technologies in ownership transfer, the legal aspects of a family constitution, and the conceptual design of a B2B CRM system. The monograph’s aim is to establish a comprehensive “Succession 4.0” framework—linking theory and practice through digital tools, career strategies, legal mechanisms, and information systems—to foster sustainable growth, competitiveness, and long-term continuity in Slovenian family enterprises.